2012
DOI: 10.1016/j.appet.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Family meals. Associations with weight and eating behaviors among mothers and fathers

Abstract: Few studies have looked at the relationship between family meals and adult weight and health behaviors. The current study investigates the association between frequency of family meals and mothers’ and fathers’ body mass index (BMI), dietary intake, dieting behaviors and binge eating. Data from Project F-EAT (Families and Eating and Activity in Teens) were used for the current analysis. Socio-economically and racially/ethnically diverse mothers and fathers (n = 3,488) of adolescents participating in a multi-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
111
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 62 publications
7
111
0
Order By: Relevance
“…Additional details on study design, data collection methods, and survey development can be found elsewhere. 28,29 All study procedures were approved by the University of Minnesota' s Institutional Review Board Human Subjects Committee and participating school districts.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Additional details on study design, data collection methods, and survey development can be found elsewhere. 28,29 All study procedures were approved by the University of Minnesota' s Institutional Review Board Human Subjects Committee and participating school districts.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Family meals may help to prevent obesity in children and adolescents (8) and some researchers have found an inverse association between family meal frequency and BMI among parents (9)(10)(11) . Fruit and vegetable consumption may also be higher among parents who eat family meals more often (12) . Studies of family meals have predominantly relied on data collected from samples of children or adolescents and their parents.…”
mentioning
confidence: 99%
“…Some have not yet been fully explored while others confirm the multidimensional nature of obesity, due to factors which influence dietary models and weight at a psycho-social and socio-economic level (Berge et al, 2012;Eisenberg, Olson, Neumark-Sztainer, Story, & Bearinger, 2004;Øvrum, Gustavsen, & Rickertsen, 2014). Among these protective factors, the frequency of family meals (FFM) plays an important role, in which there is an inverse relationship with conditions of overweight and obesity (Chan & Sobal, 2011;Mestdag, 2005;Neumark-Sztainer, Wall, Story, & Fulkerson, 2004).…”
Section: Introductionmentioning
confidence: 97%